Nacella kerguelenensis - González-Wevar, Claudio A.; Hüne, Mathias; Rosenfeld, Sebastián; Nakano, Tomoyuki; Saucède, Thomas; Spencer, Hamish; Poulin, Elie (Zenodo, 2018)
NACELLA KERGUELENENSIS (SMITH, 1879) (FIG. 10) Patella ( Patinella ) kerguelenensis Smith, 1879: 177, pl. 19, figs 13, 13a. Patella ( Nacella ) mytilina – 181, not of Helbling. Patella kerguelenensis – Watson, 1886: 27. Nacella kerguelenensis – Pilsbry, 1891: 121, pl. 49, figs 7, 8; Hedley, 1916: 44; Dell, 1964: 276; Powell, 1973: 192, pl. 173, figs 3, 4; Cantera & Arnaud, 1985: 33; González-Wevar et al. , 2010: 116; 2017: 862. Patinella kerguelenensis – Strebel, 1908: 83. Nacella mytilina – Thiele, 1912: 234, Powell, 1951: 80; 1973: 192 (in part, not of Helbling). Patinigera cf. kerguelenensis – Powell, 1955: 69. Patinigera kerguelenensis – Powell, 1957: 126. Nacella ( Patinigera ) mytilina – Cantera & Arnaud, 1985: 33 (not of Helbling) Nacella cf. mytilina – Troncoso et al. , 2001: 88 (not of Helbling). Material studied: Port-aux-Français, Kerguelen Islands (49°21’09.84’’ S, 70°13’05.89’’ E) N = 50; Port Christmas, Kerguelen Islands (48°41’40.22’’ S, 69°01’15.54’’ E) N = 60; Fjord des Portes Noires, Kerguelen Islands (49°29’47.32’’ S, 69°08’06.70’’ E) N = 50; Îles du Prince-de-Monaco, Kerguelen Islands (49°36’47.24’’ S, 69°14’11.38’’ E) N = 30; Baie des Cascades, Kerguelen Islands (49°10’02.31’’ S, 70°08’53.33’’ E) N = 30; Atlas Cove, Heard Island (53°01’27.99’’ S, 73°23’46.95’’ E) N = 10. Shell: The shell shape and sculpture are very variable in the species and two different morphotypes have been recorded at Kerguelen Islands: (1) a kelp-dweller (Fig. 10A) and (2) a hard-substrate morphotype (Fig. 10B, C). The shell and the sculpture of the hard-substrate morphotype are relatively constant in the analysed individuals, which exhibit a conical morphology, dorsally raised, with a very thick and non-translucent shell. The anterior part of the animal is laterally compressed (Fig. 10A–D). The shell is large (maximum length 120 mm) and has a medium profile. The apex is located at the the anterior 30% of the shell. All the slopes of the shell are convex. The aperture of the shell is oval. The surface of the shell is sculptured with weak radial folds. The margin of the shell is very crenulated. The external coloration varies from purplish brown to grey/white and the apex is reddish bronze. The internal part of the shell varies from light brown to purple with a metallic lustre and dark lines corresponding to external colour patterns bordered by a white/grey halo. The shell of the kelp-dweller morphotype resembles N. mytilina from the Magellanic province. This morphotype is conical, dorsally raised, with a very thin and translucent shell. The shell is of medium size (maximum length 60 mm), with a low profile. The apex is situated at the anterior 20% of the shell, anteriorly directed and curved toward the border, and obtuse. The anterior slope is concave, while the posterior and lateral ones are convex. The aperture is oval. The surface of the shell is sculptured with a few radial ribs, more obvious in the anterior zone, with concentric growth lines. The margin of the shell is relatively even. The external and internal coloration of the shell is purple to brown, with darker tones toward the apex. External anatomy (for both morphotypes): The ventral area of the foot is dark grey to black and the epipodial fringe is highly recognizable. The mantle fold is thick and dun-brown coloured. The mantle tentacles are in alternated series of three shorter pigmented ones (white/black/white) and a black longer one (Fig. 10G). The cephalic tentacles are dorsally pigmented with a black line (Fig. 10G). Radula: The first lateral teeth are set close together on the anterior edge of the basal plates, long and sharp pointed, with two cusps. The second laterals are broader with four sharp cusps (Fig. 10H). Distribution: Kerguelen and Heard Islands (Fig. 10I). Nacella kerguelenensis is highly abundant and exhibits a continuous distribution in the Kerguelen Archipelago. The species is also broadly distributed on Heard Island. Habitat: The species occurs in the high and medium intertidal rocky ecosystem down to 40 m depths; it is also abundant grazing on macroalgae. Comments: As previously mentioned, the kelpassociated morphotype of N. kerguelenensis exhibits major parallels in terms of shell morphology, thickness and sculpture, as well as habitat preferences with the Patagonian N. mytilina . Recent molecular analyses determined that this kelp-associated morphotype at Kerguelen Islands fell within the genetic diversity recorded in N. kerguelenensis (González-Wevar et al. , 2017). Accordingly, N. kerguelenesis is restricted to Kerguelen and Heard Islands (González-Wevar et al. , 2010, 2017, this revision). : Published as part of González-Wevar, Claudio A., Hüne, Mathias, Rosenfeld, Sebastián, Nakano, Tomoyuki, Saucède, Thomas, Spencer, Hamish & Poulin, Elie, 2019, Systematic revision of Nacella (Patellogastropoda: Nacellidae) based on a complete phylogeny of the genus, with the description of a new species from the southern tip of South America, pp. 303-336 in Zoological Journal of the Linnean Society 186 on pages 321-322, DOI: 10.1093/zoolinnean/zly067, http://zenodo.org/record/5718878 : {"references": ["Smith EA. 1879. Mollusca. An account of the petrological, botanical and zoological collection made in Kerguelen's Island and Rodriguez during the Transit of ' Venus' Expedition in the years 1874 - 75. Philosophical Transactions of the Royal Society of London 168: 167 - 192.", "Watson RB. 1886. Report on the Scaphopoda and Gasteropoda collected by H. M. S. Challenger during the years 1873 - 1876. Report on the Scientific Results of the Voyage of H. M. S. Challenger, 1873 - 1876, Zoology 15: 1 - 756.", "Pilsbry HA. 1891. Manual of conchology. Structural and systematic with illustrations of the species, Vol. 13. Philadelphia, PA: Academy of Natural Sciences.", "Hedley C. 1916. Report on Mollusca from elevated marine beds ' Raised Beaches' of McMurdo Sound. British Antarctic Expedition 1907 - 1909, Geology 2: 85 - 88.", "Dell, RK. 1964. Marine Mollusca from Macquarie and Heard Islands. Records of the Dominion Museum 4: 267 - 301.", "Powell AWB. 1973. The patellid limpets of the World (Patellidae). In: Abbot RT ed. Indo-Pacific Mollusca: monographs of the marine mollusks of the world with emphasis on those of the tropical western Pacific and Indian Oceans, Vol. 3. Auckland, New Zealand: Auckland Institute and Museum.", "Cantera JR, Arnaud PM. 1985. Les gasteropodes prosobranches des Iles Kerguelen et Crozet (Sud de L'Ocean Indien) comparison ecologique et particularites biologiques. CNFRA (Comite National Francais des Recherches Antarctiques) 56: 1 - 169.", "Gonzalez-Wevar CA, Nakano T, Canete JI, Poulin E. 2010. Molecular phylogeny and historical biogeography of Nacella (Patellogastropoda: Nacellidae) in the Southern Ocean. Molecular Phylogenetics and Evolution 56: 115 - 124.", "Gonzalez-Wevar CA, Hune M, Segovia NI, Nakano T, Spencer HG, Chown S, Saucede T, Johnstone G, Mansilla A, Poulin E. 2017. Following the Antarctic Circumpolar Current: patterns and processes in the biogeography of the limpet Nacella (Mollusca: Patellogastropoda) across the Southern Ocean. Journal of Biogeography 44: 861 - 874.", "Strebel H. 1908. Die Gastropoden (mit Ausnahme de nackten Opisthobranchier). Wissenschaftliche Ergebnisse der Schwedischen Sudpolar-Expedition 1901 - 1903 6: 1 - 111.", "Thiele J. 1912. Die antarktischen Schnecken und Muscheln. Deutsche Sudpolar-Expedition (1901 - 1903) 13: 183 - 285.", "Powell AWB. 1951. Antarctic and Subantarctic Mollusca: Pelecypoda and Gastropoda. Discovery Reports 26: 47 - 196.", "Powell AWB. 1955. Mollusca of the Southern Islands of New Zealand. Cape Expedition Series Bulletin N \u00b0 15. Wellington, New Zealand: Department of Scientific and Industrial Research.", "Powell AWB. 1957. Mollusca of Kerguelen and Macquarie Islands. B. A. N. Z. Antarctic Research Expedition, 1929 - 1931. Report B 6: 107 - 149.", "Troncoso N, Van Goethem JL, Troncoso JS. 2001. Contribution to the marine molluscan fauna of Kerguelen Islands, South Indian Ocean. Iberus 19: 83 - 114."]}